Combined effects of fishing and oil spills on marine fish: Role of stock demographic structure for offspring overlap with oil. Issue 1 (April 2018) - Stige, Leif Chr.; Ottersen, Geir; Yaragina, Natalia A.; Vikebø, Frode B.; Stenseth, Nils Chr.; Langangen, Øystein
Abstract: It has been proposed that the multiple pressures of fishing and petroleum activities impact fish stocks in synergy, as fishing-induced demographic changes in a stock may lead to increased sensitivity to detrimental effects of acute oil spills. High fishing pressure may erode the demographic structure of fish stocks, lead to less diverse spawning strategies, and more concentrated distributions of offspring in space and time. Hence an oil spill may potentially hit a larger fraction of a year-class of offspring. Such a link between demographic structure and egg distribution was recently demonstrated for the Northeast Arctic stock of Atlantic cod for years 1959–1993. We here estimate that this variation translates into a two-fold variation in the maximal proportion of cod eggs potentially exposed to a large oil spill. With this information it is possible to quantitatively account for demographic structure in prospective studies of population effects of possible oil spills. Highlights: We quantify maximal potential overlap between fish eggs and hypothetical oil spills. Maximal overlap is highest when the spawning stock is dominated by small fish. Fishing may thus influence sensitivity to oil spills through effect on demography. Our results can be used in prospective studies to correct for this effect.